Neodymium Laser Treatment of IOP Rise Following Ex-Press Glaucoma Device Implantation: A Retrospective Review From 4 Institutions. Issue 2 (February 2020) - Mustafa, Majd; Shoham-Hazon, Nir; Reiss, George R.; Samuelson, Thomas W.; Condon, Gary; Ahmed, Iqbal Ike K.
Abstract : Précis: Our retrospective study examined the use of neodymium laser in 53 eyes with high intraocular pressure (IOP) following Ex-Press filtration device implantation. We found a statistically significant immediate IOP-lowering effect in all eyes, with a mean IOP reduction of 13.34±8.99 mm Hg, and a posttreatment IOP of 14.30±8.57 mm Hg ( P <0.0001). Of a subset of 43 eyes on which 6 months follow-up IOP data was available, 28 eyes achieved treatment success (IOP<18 without further surgical interventions) with a mean IOP of 11.39±4.03 mm Hg at 6 months. Purpose: The purpose of this study was to report on the use of neodymium laser for treatment of eyes with IOP rise following Ex-Press glaucoma filtration device implantation. Methods: We retrospectively examined the medical records of 73 patients who underwent Ex-Press device implantation at 4 medical institutions between 2007 and 2015 and subsequently developed an IOP rise. Enrollment criteria included patients with POAG on whom posttreatment IOP data is available. Indications for treatment with neodymium laser were an IOP above target and a flat bleb. To disrupt the presumed microblockage, the neodymium laser was aimed at the axial and relief ports of the Ex-Press device. Applanation tonometry measurements were followed up after neodymium treatment for variable time intervals. Success was defined as an IOP <18 mm Hg at 6 months without further surgical or laser-based glaucoma interventions. Results: A total of 73 charts were reviewed. Twenty patients were excluded due to insufficient data or a diagnosis other than POAG. Data from 53 eyes of the remaining 53 patients was analyzed. The mean duration between Ex-Press implantation and rise in IOP requiring neodymium intervention was 34.2 months (range, 1.1 to 67.2). We found a statistically significant immediate IOP-lowering effect in all eyes, with a mean IOP drop of 13.34±8.99 mm Hg, and a mean posttreatment IOP of 14.30±8.57 mm Hg ( P <0.0001). Of a subset of 43 eyes on which 6 months follow-up IOP data was available, 11 eyes required further glaucoma intervention (surgery or laser-based); 4 eyes had an IOP of ≥18 at 6 months. In the remaining 28 successful eyes, a sustained IOP<18 mm Hg was observed at 6 months, with a mean pressure of 11.39±4.03 mm Hg ( P <0.0001). Hypotony (IOP<5) occurred in 3 eyes immediately following treatment and self-resolved by 1 week. Conclusion: Our retrospective case series suggests that neodymium laser is a potential consideration in eyes with sustained IOP rise after Ex-Press device implantation. Abstract : Supplemental Digital Content is available in the text.